2010
DOI: 10.1016/s1674-8301(10)60038-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of transforming growth factor-β1 gene variants with risk of coal workers' pneumoconiosis

Abstract: ObjectiveThe aim of this case-control study was to explore whether five tagging single nucleotide polymorphisms (tSNPs) within the transforming growth factor-β1 (TGF-β1) gene were involved in manifestation of inflammatory and fibrotic processes associated with coal workers' pneumoconiosis (CWP).MethodsThe study included 508 CWP patients and 526 controls who were underground coal miners from Xuzhou Mining Business Group. Five tSNPs were selected from the HapMap and detected by polymerase chain reaction-restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The study selection process is shown in Figure 1 . Seven of these studies investigated association between TGF-β1 −509 C>T polymorphism and pneumoconiosis,[ 15 16 17 18 19 20 21 ] nine involved +869 T>C polymorphism,[ 15 17 18 19 20 22 23 24 25 ] and five involved +915 G>C polymorphism. [ 15 17 19 20 24 ] The characteristics of each selected study are listed in Tables 1 – 3 .…”
Section: R Esultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study selection process is shown in Figure 1 . Seven of these studies investigated association between TGF-β1 −509 C>T polymorphism and pneumoconiosis,[ 15 16 17 18 19 20 21 ] nine involved +869 T>C polymorphism,[ 15 17 18 19 20 22 23 24 25 ] and five involved +915 G>C polymorphism. [ 15 17 19 20 24 ] The characteristics of each selected study are listed in Tables 1 – 3 .…”
Section: R Esultsmentioning
confidence: 99%
“…Specifically, Table 1 shows characteristics of case and control for association of −509 C>T polymorphism with pneumoconiosis, six of which were performed in Asia. [ 15 17 18 19 20 21 ] One was performed in Caucasus,[ 16 ] originating from China and USA, respectively. Pneumoconiosis was induced by coal in two studies, and others were induced by silicosis.…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some sensitive biomarkers, including transforming growth factor-β1 (TGF-β1) and ceruloplasmin (CP), which had been found able to detect the pulmonary inflammation and fibrosis induced by occupational exposure to asbestos or other toxicants. TGF-β1 is a multifunctional cytokine that is critically involved in the pathogenesis of fibrosis and contributes to the influx and activation of inflammatory cells [ 13 , 14 ]. Previous studies found that TGF-β1 plays a key role in the development of lung fibrosis, and the expression of TGF-β1 increases in lung tissue of patients with lung fibrosis and animal models of pulmonary fibrosis [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…prolonged lung inflammation and fibrotic nodular lesions that usually lead to progressive fibrosis [5]. Although silica dust exposure is recognized as the primary cause of pneumoconiosis, extensive researches indicate that genetic factors have played important roles in the development of pulmonary fibrosis [2,[6][7][8]. During the past four decades in China, CWP continues to occur even though work environment and prevention measures have been greatly improved [9], and still more than 23 million workers exposed to silica particles [10].…”
Section: Introductionmentioning
confidence: 99%